On the impact of liquisol quenching on the structure of a double hcp gold-cadmium-indium alloy - Ramachandrarao P.; Lele S.; Rama Rao P. (My University, 2025)
The effect of quenching from the liquid state a gold alloy containing 17.5 at.% cadmium and 5.0 at.% indium with the double hexagonal close-packed (dhcp) structure was investigated. With qualitatively differing cooling-rates three metastable close-packed layer structures, namely face-centred cubic, hexagonal close-packed and samarium-type, were obtained. On annealing, the metastable phases were observed to retransform to the equilibrium dhcp phase. © 1973 Chapman and Hall Ltd.